2020
DOI: 10.2147/prbm.s240827
|View full text |Cite
|
Sign up to set email alerts
|

<p>Suicidal Behavior and Associated Factors Among Students in Mettu University, South West Ethiopia, 2019: An Institutional Based Cross-Sectional Study</p>

Abstract: Point your SmartPhone at the code above. If you have a QR code reader the video abstract will appear. Or use: https://youtu.be/VnFTiTuzCpI Background: Suicidal behavior is a leading cause of injury and death worldwide. It is a public health issue that is estimated to contribute more than 2.4% to the global burden of disease by the year 2020. University and college students are among groups affected more than the general population. However, there is a scarcity of studies on the magnitude and associated factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
66
6
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 28 publications
12
66
6
8
Order By: Relevance
“…Psychological problems in response to COVID-19 have been expected ( Lee et al., 2020b ); as during disease outbreaks, people may develop depressive symptoms and anxiety following reports of deaths, increased media communications, and an escalating number of new cases ( Lahav, 2020 ). This study showed that suicide risk was associated with depression and anxiety, which is in agreement with the results of other published studies ( Abdu et al., 2020 ; Eskin et al., 2016 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Psychological problems in response to COVID-19 have been expected ( Lee et al., 2020b ); as during disease outbreaks, people may develop depressive symptoms and anxiety following reports of deaths, increased media communications, and an escalating number of new cases ( Lahav, 2020 ). This study showed that suicide risk was associated with depression and anxiety, which is in agreement with the results of other published studies ( Abdu et al., 2020 ; Eskin et al., 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of suicide ideation was slightly higher in the present study than that reported among US residents during the COVID-19 pandemic (19.0% vs. 17.5%) (Ammerman et al, 2020). In a recent, pre-COVID-19 study conducted among university students in South West Ethiopia, the lifetime prevalence of suicidal ideation, planning, and attempting was reported to be 58.3%, and 37.3%, respectively (Abdu et al, 2020). The prevalence of suicidal behaviors (i.e., suicide ideation and planning) differs across studies, depending on the language and the methods used for the study as well as the duration of the study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The possible justification for this association could be the fact that when grade point average decreases, the student might consider suicidal ideation due to feeling of hopelessness, worthlessness, fear of failure and doubts about academic competence [43]. A frequent suicidal ideation has also been linked with depression, which in turn affects attention and concentration span and negatively impacts the ability to learn, understand, and solve academic problems [44].…”
Section: Plos Onementioning
confidence: 99%
“…This finding was inconsistent with the study done on mettu university students. 33 Living in a rural residence might contribute to strong cultural and social in-acceptability of attempting suicide. Those who were WHO stage of HIV stage IV were 5.65 times more likely to attempt suicide than those in stage I (AOR=5.65; 95% CI: 2.14, 14.93).…”
Section: Discussionmentioning
confidence: 99%